+0  
 
0
9
2
avatar+34 

Compute \(i^{-100}+i^{-99}+i^{-98}+...+i^{-1}+i^{0}+i^{1}+...+i^{99}+i^{100}\)

 

I got 0 but it was incorrect. I think I might be doing something wrong. Thanks!

 Mar 30, 2024
 #1
avatar+359 
-1

Let's break it down step-by-step:

 

Grouping Terms:

 

We notice that the series alternates between terms with a negative imaginary unit exponent (i^-n) and terms with a positive imaginary unit exponent (i^n). This allows us to group the terms together:

 

(i^-100 + i^-99 + ... + i^-1) + (i^0 + i^1 + ... + i^99 + i^100)

 

Simplifying Each Group:

 

First Group:

 

In this group, all the terms except the first (i^-100) and the last (i^-1) will cancel out because i raised to any negative power is the same as its reciprocal multiplied by i^-1.

 

Therefore, the first group simplifies to: i^-100 + i^-1

 

Second Group:

 

Similarly, in the second group, all the terms except the first (i^0) and the last (i^100) will cancel out because for any non-zero integer n, i^n * i^-n = i^(n-n) = i^0 = 1.

 

Therefore, the second group simplifies to: 1 + i^100

 

Recombining and Simplifying:

 

Now, we have the simplified version of the series:

 

(i^-100 + i^-1) + (1 + i^100)

 

i^-100 can be simplified as 1/i^100 (since i raised to any negative power is the reciprocal).

 

i^-1 = -i (because i raised to the odd power -1 is -i).

 

Putting it all together:

 

(1/i^100 - i) + (1 + i^100)

 

Analyzing i^100:

 

The key here is to recognize that i raised to any multiple of 4 results in 1 (i^4 = (i^2)^2 = (-1)^2 = 1). Since 100 is a multiple of 4, i^100 = 1.

Final Simplification:

 

(1/i^100 - i) + (1 + i^100) becomes:

 

(1/1 - i) + (1 + 1)

 

Simplifying further: (1 - i) + 2

 

Combining like terms: 1 - i + 2

 

Final result: 3 - i

 

The sum is 3 - i.

 Mar 30, 2024
 #2
avatar+128794 
+1

i^1 + i^2 + i^3 + i^4  = 

i + -1   - i  + 1  =  0

And this  pattern will repeat  

So....sum  of   i^1  tp  i^100 inclusive =  0

 

i^(-1)  = 1 / i  =   i / i^2  =  -i

i^(-2) = 1/i^2  = 1/ -1 = -1

i^(-3)  =  1/^2  * 1/i  =  -1 * 1/i =  -1 *-i  =  i

i^(-4) = 1/I^2  * 1/i^2 =  -1 * -1  = 1

And this pattern  will repeat

So....sum of i^(-100)  to i^(-1)  inclusive  = 0 

 

The only term not evaluated is i^0   =  1

 

So....the sum will be  1

 

cool cool cool

 Mar 31, 2024

1 Online Users

avatar